STUDY OF ENVIRONMENTAL GEOLOGY FOR URBAN DEVELOPMENT PLANING IN METROPOLITAN AREA OF NORTH SEMARANG CITY, CENTRAL JAVA PROVINCE - Adham, Helmi
Based on PP No. 78 of 2017 about Urban Spatial Planning, a new metropolitan area was formed called the Kedungsepur area (Kendal, Demak, Ungaran, Salatiga, Semarang, and Purwodadi) with the center located in Semarang City. The National Spatial Policy places the Kedungsepur Urban Area as a Kawasan Strategis Nasional (KSN) with a focus on Rehabilitation/Revitalization area with an Economic Interest. The results of the establishment of this new metropolitan area finally needed a study of environmental geology, especially in the Semarang City as the center of the metropolitan area to understand the condition of geological resources, geological hazards, and land capabilities to accommodate the development of infrastructure support while at the same time accommodating the increase in population due to massive urbanization. The research area is located at 423000-440000 mE and 9234000-9222000 mN (UTM WGS 1984 Zone 49S) which is administratively located in Tugu, Ngaliyan, Candisari, Gayamsari, North Semarang, Central Semarang, South Semarang, West Semarang and East Semarang Districts. The analysis in this study uses secondary data in the form of thematic maps from research conducted by Pusat Airtanah dan Geologi Tata Lingkungan, Pusat Vulkanologi dan Mitigasi Bahaya Geologi, Badan Informasi Geospasial, and Kementerian Lingkungan Hidup dan Kehutanan. The data is then used in the preparation of the Analytical Hierarchy Process method with parameters that have been adjusted to the geological conditions in Semarang City and then digitized to produce an overlayed map of the geological parameters of the urban environment. There are thirteen environmental geological parameters used for urban area planning, both geological and non-geological. these parameters include rock and soil surface capacity, slope, ground movement vulnerability, earthquake hazard areas, volcanic hazard areas, tsunami hazard areas, liquefaction potential hazards, abrasion zones, fault zone, groundwater productivity potential, groundwater surface depth, groundwater conservation zone, protected forest areas, and airport locations. Based on the results of the environmental geological analysis, there are five classifications zones for the feasibility level of development in the research area vii with a percentage of the area covering the unrestricted zone (17%), less free zone (3%), moderately free zone (32%), fairly free zone (27 %), and free zone (21%) with the direction of development towards the southern region of the research area.